Simulation of manufacturing processes and manufacturing chains using finite element techniques - Afazov, Shukri (2009)
This thesis presents work on the simulation of manufacturing chains, simulation of manufacturing processes (casting, forging, shot-peening and heat treatment) and fatigue life prediction by using the finite element method (FEM). The objectives and the contributions of this thesis consist of development of mathematical algorithms and techniques for mapping and transferring FE data (stresses, strains, displacements, etc.) from macro-to-macro and micro-to-macro FE models among different FE solvers and meshes. All these features have been implemented into a new finite element data exchange system (FEDES). FEDES has been developed to simulate manufacturing chains by using FE techniques. Extensive research has been carried out on the simulation of investment casting processes of aero-engine parts under equiaxed and directional cooling. Methodologies for predicting the component life undergoing low cycle fatigue (LCF) and high cycle fatigue (HCF) have been developed. Life prediction based on the effect of the residual stresses obtained from micro machining and shot-peening processes has been investigated.